Genetically predicted circulating concentrations of micronutrients and risk of autoimmune thyroiditis: a Mendelian randomized study - Qiu, Rongliang; Sha, Xuemei; Kuang, Penghao; Chen, Fangsen; Fu, Jinbo (Frontiers in Immunology, 2024)
Background: Micronutrients play pivotal roles in modulating various aspects of the immune response. However, the existing literature on the association between micronutrients and autoimmune thyroiditis (AIT) remains limited and contentious. To address this gap, we conducted Mendelian randomization (MR) to investigate potential links between genetically predicted concentrations of six micronutrients (Copper (Cu), Iron (Ir), Calcium (Ca), Vitamin D (VD), Vitamin C (VC), Zinc (Zn) ) and the risk of AIT. Method: Utilizing summary statistics from genome-wide association studies (GWAS) in individuals of European descent, we employed MR methodologies to elucidate the interplay between micronutrients and AIT. Three distinct Mendelian randomization techniques were employed: Inverse Variance Weighted (IVW), MR-Egger regression, and Weighted Median Estimator (WME). Additionally, we evaluated outcome heterogeneity using Cochran's Q statistic and assessed pleiotropy using the MR-Egger intercept.Result: IVW analysis revealed no substantial evidence supporting a significant impact of genetically predicted micronutrient concentrations on AIT risk